Post-gastrectomy anemia and ferritin dynamics: key determinants of prognosis and clinical management in patients with gastric cancer - Kim, Eun Young; Song, Kyo Young; Kim, Dong Jin (Frontiers in Oncology, 2025)
ObjectiveThis study identified the trends and clinical significance of anemia and ferritin status 1 year postoperatively in patients with long-term survival and analyzed clinicopathological factors and preoperative nutritional/inflammatory conditions associated with anemia of chronic disease (ACD) development.MethodsBetween March 2009 and December 2018, 2,976 patients who underwent curative gastrectomy for gastric cancer without recurrence or mortality within postoperative 1 year were included. The patients were categorized into four groups; non-iron deficiency without anemia, iron deficiency without anemia, iron deficiency anemia (IDA), and ACD based on postoperative 1 year ferritin and hemoglobin.ResultsThe overall incidence of anemia was 36.5% (n=1,086). The prevalence of IDA and ACD was 12.7% (n=377) and 23.8 (n=709), respectively, at postoperative 1 year. Patients with ACD were significantly older, had higher ECOG, increased early complications, and were at a more advanced stage than the other groups. The overall survival (OS) of ACD was significantly lower than that of the other groups (p < 0.001), especially for stages I and III. The presence of ACD was a significant risk factor for overall (hazard ratio [HR] = 1.832, p < 0.001), disease-free (HR= 1.714, p = 0.003), and cancer-specific (HR= 1.690, P = 0.015) survival. Older age, advanced disease stage, low preoperative prognostic nutritional index, preoperative anemia, and early postoperative complications were significant risk factors for ACD.ConclusionsRelationship between ferritin and Hb at postoperative 1 year is a significant prognostic factor for survival in patients with gastric cancer. Particularly, ACD may be a specific predictor of gastric cancer. Therefore, clinicians need to pay attention to ACD status and prevent the risk factors for its development during long-term postoperative follow-up.